(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2020)
This article reads together the work of Yvonne Rainer and Carolee Schneemann, as situated between film, performance, as well as dance and painting, considering what their work reveals about a specific intermedial feminist aesthetics developing at this time. It argues these traits in their work are not isolated commonalities but are shared with a wide range of feminist artists working in the 1960s and 1970s and are still echoed in contemporary feminist art. Further the article proposes to think through these intermedial relationalities as a mode of feminist aesthetics. It argues Schneemann and Rainer successfully extend the position of the female body in cinema beyond the traditional role as object to include both an embodied form of authorship, and a complex, affective performance of woman onscreen and provides the historical foundation and influence for my reading of the embodied, intermedial experiments found in feminist experimental film and media in the ensuing decades. The comparative reading of Schneeman’s film Plumb Line and Rainer’s film Lives of Performers index the artists’ shared positioning of their own bodies in the dual roles of performer and author within their films. In my analysis, this aesthetic innovation actively engages with the different embodiments of the artist/performer, the bodies onscreen and the embodied spectator the films address.